Penerapan Metode Activity Based Costing dalam Menentukan Tarif Rawat Inap di Rumah Sakit Wava Husada Kepanjen Kabupaten Malang - Muhammad Zaki Pradana (Jurnal Syntax Admiration, 2024)
One of the hospital's revenues comes from inpatient services, so the determination of inpatient rates is one of the important aspects that need to be considered. So far, many hospitals in Indonesia still use conventional methods in determining hospitalization rates, although these methods often cause inefficient rates. This study aims to examine the application of the Activity Based Costing (ABC) method in determining hospitalization rates at Wava Husada Hospital, identify the obstacles faced in the implementation of the method, and find solutions to overcome these obstacles. This research is a type of qualitative research. The type of data used in this study is secondary qualitative data obtained from respondents through interviews and observations. The data analysis technique used is descriptive analysis. The results of this study show that the hospitalization rate at Wava Husada Hospital based on the ABC method provides greater results in classes VIP B, VIP C, I A, I B, II A, and II B and III and gives lower results in class, and class VVIP A. The price difference occurs because the ABC method charges overhead costs on each product in more detail. The implication of the study is that the results of the implementation of the hospitalization rate of Wava Husada Hospital Kepanjen Malang Regency with the ABC method can be used as a reference for Wava Husada Hospital to determine the hospitalization rates of classes VVIP A, VIP B, VIP C, I A, I B, II A, II B, and III so that it can be more efficient and accurate.